Cytoplasmic delivery of quantum dots via microelectrophoresis technique. Issue 11 (11th March 2021) - Han, Mengke; Zhao, Jiangbo; Fabian, Joseph Mahandas; Evans, Samuel; Mustafa, Sanam; Ruan, Yinlan; Wiederman, Steven; Ebendorff‐Heidepriem, Heike
Abstract: Nanoparticles with specific properties and functions have been developed for various biomedical research applications, such as in vivo and in vitro sensors, imaging agents and delivery vehicles of therapeutics. The development of an effective delivery method of nanoparticles into the intracellular environment is challenging and success in this endeavor would be beneficial to many biological studies. Here, the well‐established microelectrophoresis technique was applied for the first time to deliver nanoparticles into living cells. An optimal protocol was explored to prepare semiconductive quantum dots suspensions having high monodispersity with average hydrodynamic diameter of 13.2–35.0 nm. Micropipettes were fabricated to have inner tip diameters of approximately 200 nm that are larger than quantum dots for ejection but less than 500 nm to minimize damage to the cell membrane. We demonstrated the successful delivery of quantum dots via small electrical currents (–0.2 nA) through micropipettes into the cytoplasm of living human embryonic kidney cells (roughly 20–30 μm in length) using microelectrophoresis technique. This method is promising as a simple and general strategy for delivering a variety of nanoparticles into the cellular environment.